THE IMPACT OF FINANCIAL PERFORMANCE AND CAPITAL STRUCTURE RATIOS ON STOCK RETURNS: EVIDENCE FROM THE INDONESIAN STOCK MARKET - Gun Budiarsyah, Gun (Fortunate Business Review, 2025)
This study examines the impact of profitability, liquidity, and leverage ratios on stock returns of non-financial firms listed on the Indonesia Stock Exchange (IDX) from 2011 to 2023. Grounded in agency theory, the research investigates how financial performance indicators—Return on Assets (ROA), Return on Equity (ROE), Current Asset ratio (CUR), and Leverage (LEV)—serve as signals that influence investor perceptions and stock price movements. A quantitative causal research design was applied using panel data regression with growth opportunities and dividend payout ratio as control variables. The empirical results reveal that ROA, ROE, and CUR have a positive and significant effect on stock returns, indicating that firms with higher profitability and adequate liquidity are more likely to generate superior market performance. Conversely, leverage exhibits a positive but statistically insignificant relationship, suggesting that debt levels are less relevant in driving stock returns within the Indonesian market context. Control variables also demonstrate positive associations, emphasizing their supportive role in shaping investor expectations. These findings highlight the importance for managers to optimize profitability and liquidity management to enhance shareholder value, while maintaining prudent debt levels to mitigate financial risks.